“INCONGRUENCIAS EN CUANTO A LA COMPARECENCIA DEL ACUSADOR PARTICULAR A LA AUDIENCIA DE JUICIO Y LA VULNERACION DEL DERECHO A LA DEFENSA” - Hurtado Mendoza, José Marcelo (2021)
In this thesis entitled: "INCONGRUENCES AS TO THE APPEARANCE OF THE PARTICULAR ACCUSER AT THE TRIAL HEARING AND THE VIOLATION OF THE RIGHT TO DEFENSE"; It concerns a subject that studies a social and legal problem that arises that is generated by violating the rights of the private prosecution by not determining the appearance at the trial hearing established in the Comprehensive Organic Criminal Code; It may be feasible to attend and intervene at the trial hearing through a judicial attorney, and not unrestrictedly the private accuser in a personal way, thus guaranteeing their rights and administration in a timely manner, with agility. This problem has been verified through the development of the heading of literature review, application of surveys and interviews, verification of objectives and contrasting of the hypothesis, in which its existence was concluded and the feasibility of making a reform proposal to the Comprehensive Organic Code Criminal, in which it is stipulated that the private accuser can appear personally or through his defender or public defender, sponsor or judicial attorney to the trial hearing without any exception, without mediating the abandonment as currently stipulated in the criminal regulations current.